Cross-talk of MLST and transcriptome unveiling antibiotic resistance mechanism of carbapenem resistance Acinetobacter baumannii clinical strains isolated in Guiyang, China - Qiu, Zhilang; Yuan, Kexin; Cao, Huijun; Chen, Sufang; Chen, Feifei; Mo, Fei; Guo, Guo; Peng, Jian (Frontiers in Microbiology, 2024)
Acinetobacter baumannii (A. baumannii) is an important opportunistic pathogen causing nosocomial infection in the clinic. The occurrence rate of antibiotic resistance is increasing year by year, resulting in a highly serious situation of bacterial resistance. To better understand the local epidemiology of multidrug-resistant A. baumannii, an investigation was conducted on the antibiotic resistance of different types of A. baumannii and its relationship with the genes of A. baumannii. Furthermore, the molecular mechanism underlying antibiotic resistance in A. baumannii was investigated through transcriptome analysis. These results showed that a total of 9 STs were detected. It was found that 99% of the strains isolated in the hospital belonged to the same STs, and the clone complex CC208 was widely distributed in various departments and all kinds of samples. Furthermore, these A. baumannii strains showed high resistance to ertapenem, biapenem, meropenem, and imipenem, among which the resistance to ertapenem was the strongest. The detection rate of blaOXA-51 gene in these Carbapenem resistance A. baumannii (CRAB) reached 100%; Additionally, the transcriptome results showed that the resistance genes were up-regulated in resistance strains, and these genes involved in biofilm formation, efflux pumps, peptidoglycan biosynthesis, and chaperonin synthesis. These results suggest that the CC208 STs were the main clonal complex, and showed high carbapenem antibiotic resistance. All these resistant strains were distributed in various departments, but most of them were distributed in intensive care units (ICU). The blaOXA-23 was the main antibiotic resistance genotype; In summary, the epidemic trend of clinical A. baumannii in Guiyang, China was analyzed from the molecular level, and the resistance mechanism of A. baumannii to carbapenem antibiotics was analyzed with transcriptome, which provided a theoretical basis for better control of A. baumannii.